2003
DOI: 10.1016/s0304-4017(03)00137-7
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of canine dirofilariosis in South Korea

Abstract: Eight-hundred and forty eight dogs (480 females and 368 males) not on chemoprophylaxis were examined for Dirofilaria immitis infection from 2001 to 2002. Three-hundred and thirty nine (40.0%) of 848 samples tested with antigen detecting ELISA kits showed positive reaction for D. immitis antigen. More male (43.5%) than female (37.3%) dogs were affected in this study, although there was no significant difference between both groups. Chi2 analysis showed that female and male dogs of shoreline areas had higher sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 6 publications
4
23
1
3
Order By: Relevance
“…Both sexes had similar prevalence (P>0.05) in agreement with several authors (Song et al, 2003;Montoya et al, 2006;Rapti and Rehbein, 2010), which is in contrast to other studies (Yldrim et al, 2007;Traversa et al, 2010), where significantly higher prevalence rates in males were shown. It has been suggested that the higher infection rate in male dogs could be due to them attracting vectors more strongly (Montoya et al, 1998).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Both sexes had similar prevalence (P>0.05) in agreement with several authors (Song et al, 2003;Montoya et al, 2006;Rapti and Rehbein, 2010), which is in contrast to other studies (Yldrim et al, 2007;Traversa et al, 2010), where significantly higher prevalence rates in males were shown. It has been suggested that the higher infection rate in male dogs could be due to them attracting vectors more strongly (Montoya et al, 1998).…”
Section: Discussioncontrasting
confidence: 56%
“…Several studies found older dogs having an increased risk of D. immitis infection that was thought to be due to the prepatency period of the parasite (Song et al, 2003;Tudor et al, 2009;Lim et al, 2010;Vieira et al, 2014). According to the literature (Montoya et al, 1998;Yildirim et al, 2007) another important risk factor is the time of exposure to the vector; in fact these dogs were kept in outdoor shelters, where they were more likely to acquire this infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that outdoor dogs are more frequently bitten by mosquitoes than are indoor dogs. A survey by Song et al (2003) confirmed that the prevalence of dirofilariasis in shoreline areas was significantly higher (69.5%) than that in other areas (urban or mountain areas). Outdoor dogs in Busan also evidenced the highest prevalence (48.4% of adult worms and 35.9% of microfilaria) among dogs examined in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, the prevalence of heartworm infection in several regions of Korea was found to correspond to an infection rate of 40.0%, according to the results of antigen tests conducted between 2001 and 2002 (Song et al, 2003). These reports showed that Korea is an endemic area of dirofilariasis.…”
Section: Introductionmentioning
confidence: 90%
“…The parasite is widely distributed in Africa, Asia, Australia, Latin America and Mediterranean countries (3,6,10,12,17,24). Turkey is suitable country for development of this parasite due to climatic conditions and abundant intermediate hosts.…”
Section: Introductionmentioning
confidence: 99%